2012
DOI: 10.3758/s13423-012-0345-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of regular aerobic exercise for executive functioning in healthy populations

Abstract: Research suggests that regular aerobic exercise has the potential to improve executive functioning, even in healthy populations. The purpose of this review is to elucidate which components of executive functioning benefit from such exercise in healthy populations. In light of the developmental time course of executive functions, we consider separately children, young adults, and older adults. Data to date from studies of aging provide strong evidence of exercise-linked benefits related to task switching, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
257
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(284 citation statements)
references
References 93 publications
19
257
3
5
Order By: Relevance
“…In the healthy population, aerobic exercise can improve executive functions like task switching, selective attention, working memory updating, and inhibitory control in children and young adults (Guiney and Machado 2013). Cardiovascular fitness positively associates with intelligence assessed using tests for logical, verbal, and technical skills (Aberg et al 2009;Moore et al 2014), with increased cognitive flexibility and improved action monitoring process (Themanson et al 2008;Hillman et al 2008), and with improvement in academic achievements (Chaddock-Heyman et al 2013;Chaddock et al 2012).…”
Section: Human Neurogenesis Cognition and Exercisementioning
confidence: 99%
“…In the healthy population, aerobic exercise can improve executive functions like task switching, selective attention, working memory updating, and inhibitory control in children and young adults (Guiney and Machado 2013). Cardiovascular fitness positively associates with intelligence assessed using tests for logical, verbal, and technical skills (Aberg et al 2009;Moore et al 2014), with increased cognitive flexibility and improved action monitoring process (Themanson et al 2008;Hillman et al 2008), and with improvement in academic achievements (Chaddock-Heyman et al 2013;Chaddock et al 2012).…”
Section: Human Neurogenesis Cognition and Exercisementioning
confidence: 99%
“…Studies of healthy humans have found positive effects of exercise on cognitive measures in both children, younger adults, and elderly populations (see e.g. Guiney and Machado 2013, Hopkins et al 2012, Khan and Hillman 2014. Furthermore, findings from human studies suggest a beneficial effect of physical exercise regarding prevention of age-related cognitive impairment and potentially even development of Alzheimer's disease (Erickson et al 2011, Laurin et al 2001, Lindsay et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity benefits many parts of the body and can reduce many of the risk factors for non-communicable diseases (Guiney & Machado, 2013;Mezzani et al, 2013). The need exists for a fast, noninvasive and accessible tool that recreational athletes could use to evaluate and categorise health-related fitness, and track their progress.…”
Section: Introductionmentioning
confidence: 99%